Spatial dispersion statistics and sequential sampling plan for leaf spot disease caused by Colletotrichum lindemuthianum in French bean - and G.D. SHARMA, G.K.N. CHHETRY, R.R. MISHRA (Indian Phytopathology, 2002)
Iwao's patchiness regression technique was used to study the spatial distribution of Colletotrichum lindemuthianum infecting French bean leaves. The dispersion statistics indicates that the basic components of the disease lesion population aggregates and is contagiously distributed in French bean. Fungicides spray did not alter this distribution. The dispersion statistics worked out enabled to arrive at sequential sampling plan that requires a maximum of 54 leaves 'sample to assess distribution pattern. A preliminary economic threshold of one lesion per leaf was used to prepare the sampling plan.